Elucidating pathways to pediatric obesity: a study evaluating obesity polygenic risk scores related to appetitive traits in children - Renier, Timothy J.; Yeum, Dabin; Emond, Jennifer A.; Lansigan, Reina K.; Ballarino, Grace A.; Carlson, Delaina D.; Loos, Ruth J. F.; Gilbert-Diamond, Diane (International Journal of Obesity, 2024)
Obesity polygenic risk scores (PRS) explain substantial variation in body mass index (BMI), yet associations between PRSs and appetitive traits in children remain unclear. To better understand pathways leading to pediatric obesity, this study aimed to assess the association of obesity PRSs and appetitive traits. This study included 248 unrelated children aged 9-12 years. DNA from the children was genotyped (236 met quality control thresholds) and four weighted polygenic risk scores from previous studies were computed and standardized: a 97 SNP PRS, 266 SNP pediatric-specific PRS, 466 SNP adult-specific PRS, and ~2 million SNP PRS. Appetitive traits were assessed using a parent-completed Child Eating Behavior Questionnaire, which evaluated food approach/avoidance traits and a composite obesogenic appetite score. BMI was directly measured and standardized by age and sex. Three associations were evaluated with linear regression: (1) appetitive traits and BMI, (2) PRSs and BMI, and (3) PRSs and appetitive traits, the primary association of interest. Expected positive associations were observed between obesogenic appetitive traits and BMI and all four PRSs and BMI. Examining the association between PRSs and appetitive traits, all PRSs except for the 466 SNP adult PRS were significantly associated with the obesogenic appetite score. Each standard deviation increase in the 266 SNP pediatric PRS was associated with an adjusted 2.1% increase in obesogenic appetite score (95% CI: 0.6%, 3.7%, p = 0.006). Significant partial mediation of the PRS-BMI association by obesogenic appetite score was found for these PRSs; for example, 21.3% of the association between the 266 SNP pediatric PRS and BMI was explained by the obesogenic appetite score. Genetic obesity risk significantly predicted appetitive traits, which partially mediated the association between genetic obesity risk and BMI in children. These findings build a clearer picture of pathways leading to pediatric obesity.